Relation confraternelle entre interne et sénior: modèle d'inspiration bubérienne - Pougnet, Richard (Journal international de bioéthique et d'éthique des sciences, 2016)
Doctors in training work in services under the supervision of senior doctors. These professional relationships may lead to frustrations, or ill-being at work. Indeed doctors are often very busy with care and can hardly communicate. The purpose of this article is to propose ways to think in its ethical dimension this relationship, by learning from Martin Buber’s ideas. He thought a philosophy of relationship in two word pairs: I-Thou and I-It. This thought can be useful in the context of the médical relationship and mentorship. Indeed we can see our colleague as a person or only as a caregiver. We offer a relationship model according to buberian thought, between junior and senior doctor caring about the same patients.